Conversor híbrido com capacitores flutuantes e pernas magneticamente acopladas - Romani, Junior (2019)
This work presents a general analysis for multilevel converters with flying capacitors and parallel legs. For each converter leg, multilevel structures containing flying capacitors connected in parallel via coupled inductors are used. The usage of decoupled inductors presents the advantage of modularity, whereas coupled inductors have the advantage of suppressing circulating currents and simultaneously providing negligible impedance for the output current. Additionally, coupled inductors present unique output between the converters legs. The usage of different turn ratios between the coupled inductors windings performs a balancing between the converters legs, generating new combinations and increasing the number of output levels of the converter. On the other hand, connecting legs in parallel has the consequence of generating circulating currents which leads to higher stresses and extra losses on the active and passive components of the circuit, being necessary the utilization of techniques for minimizing these circulating currents. Topologies with asymmetric flying capacitors apply different voltage levels on the flying capacitors to synthesize a higher number of output levels. In these converters, the flying capacitors voltages regulation is a pre-requisite for the correct operation of the converter, being necessary the usage of control and modulation techniques that meet this requisite. In this context, this work presents an analysis related to converters with magnetic coupled flying capacitors. From the analysis, techniques for balancing the flying capacitors as well as for regulating and mitigating the circulating currents are proposed. The employment of vector modulation allows to use the converters redundancies to meet the pre-requisites of the operation. To validate the analysis, simulation and experimental results are shown.